Retinal Changes in an ATP-Induced Model of Retinal Degeneration - Aplin, Felix P.; Vessey, Kirstan A.; Luu, Chi D.; Guymer, Robyn H.; Shepherd, Robert K.; Fletcher, Erica L. (Frontiers in Neuroanatomy, 2016)
In rodents and felines, intravitreal administration of adenosine triphosphate (ATP) has been shown to induce photoreceptor death providing a tractable model of retinal degeneration in these species. This study investigated the long term effects of photoreceptor loss in an ATP induced feline model of retinal degeneration. Six normal sighted felines were unilaterally blinded using intravitreal ATP injections and assessed using electroretinography (ERG) and optical coherence tomography (OCT). At 30 h (n = 3) or 12 weeks (n = 3) post-injection, the animals were euthanized and the eyes enucleated. Retinae were sectioned and labeled using immunohistochemistry for markers of cell death, neural remodeling and gliosis. Ongoing cell death and retinal degeneration was observed in the outer retina at both 30 h and 12 weeks following unilateral ATP injection. Markers of mid to late-stage retinal remodeling such as cell displacement and aberrant neurite growth were observed in the inner retina at 12 weeks post-injection. Ganglion cells appeared to remain intact in ATP injected eyes. Müller cell gliosis was observed throughout the inner and outer retina, in some parts completely enveloping and/or displacing the surviving neural tissue. Our data suggests that the ATP injected feline retina continues to undergo progressive retinal degeneration and exhibits abnormalities consistent with a description of retinal remodeling commonly seen in other models of retinal degeneration. These findings validate the use of intravitreal ATP injection in feline as a large animal model of retinal degeneration which may aid in development of therapies aiming to restore visual function after photoreceptor degeneration.